Structure-function mimicry of oxidized purple acid phosphatase-PAP(ox)-A new functional model - Waghmode, Shobha A.; Date, Sadgopal K.; Gupta, Vidya S.; Rane, Sandhya Y. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
{Electronic structure and spectroscopic properties of the novel diiron active site of oxidized mammalian purple acid phosphatase analogues, Fe-6: [Fe-2 (mu-O) (mu-OAc) (4HNSQ(ox))(2 center dot-)(ONSQ(ox))(2 center dot-)(H2O)(4)] and Fe-7: [Fe-2 (mu-O) (mu-OAc)(ONSQ(ox))(2 center dot-)(OAc) (H2O)(4)] are described. Magnetic susceptibility SQUID data of Fe-6 are best fitted to Heisenberg's isotropic spin pair (S = 5/2, 3/2) model using magnetic parameters g = 2 and J = - 36.8 cm(-1) with R factor = 6.4 x 10(-4). The antiferromagnetic exchange establishes Fe(III)-O-Fe(III) dimeric core with Fe(III) site having two radical ligations in the naphthosemiquinone oxime form of lawsone oxime. In the model compound Fe-7 of oxidized purple acid phosphatase, bridged and terminal acetate functions are identified according to their different energies of activations, i.e, similar to 34 and 58 kJ mol(-1) respectively. Also, the reduced naphthoquinone oxime form of ligand is characterized by its energy of activation (similar to 15 kJ mol(-1)) from pyrolytic reaction. Mossbauer parameters
Keywords: Antiferromagnetic exchange; Bioinorganic chemistry; DNA cleavage; iron; Nuclease activity; PAP(ox) analogues